Agglomeration of celecoxib by quasi-emulsion solvent diffusion method without stabilizer: effect of good solvent. (26th November 2018) - Maghsoodi, Maryam; Nokhodchi, Ali
Abstract: Aim: The aim of the present research is to investigate the feasibility of agglomeration of crystals by the quasi-emulsion solvent diffusion method without using a stabilizer. Method: Two solvent systems comprising a solvent and an antisolvent (water) were used to prepare celecoxib agglomerates. To this end, seven solvents including propanol, methyl acetate, methyl ethyl ketone, butanol, ethyl acetate, isopropyl acetate, and pentanol were examined. The agglomerates were evaluated by micromeritic properties (e.g., size, density, flowability), yield, drug physical state, friability, and dissolution behavior. Results: In the present study the clear trend was observed experimentally in the agglomerate properties as a function of physical properties of the solvent such as miscibility with water. Solvents with high water miscibility (25% v/v) resulted in sticky and hollow particles, while solvents with low water miscibility (3%v/v) led to the formation of agglomerates with low strength. However, the agglomerates made from the solvents with intermediate water miscibility (10% v/v), may reflect a greater integrity of the agglomerates regarding yield and strength. Conclusion: Results of this study offer a useful starting point for a conceptual framework to guide the selection of solvent systems for the quasi-emulsion solvent diffusion method without using a stabilizer.